PENINGKATAN KEMAMPUAN MENGENAL ANGKA MELALUI MEDIA GAME EDUKASI MENGGUNAKAN SMART BOARD DI TAMAN KANAK-KANAK MELATI KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA - Riza Mastia; Vivi Anggraini; Serli Marlina; Saridewi (STKIP Subang, 2026)
This study aimed to improve children's number recognition skills through educational game media using a smart board at Melati Kindergarten, Mungka District. The research was conducted because children's ability to recognize and write numbers was still low, partly due to the limited use of instructional media in the learning process. The method used in this study was Classroom Action Research (CAR), consisting of two cycles: planning, implementation, observation, and reflection. Data were collected through observation, documentation, tests, and assignments.The results showed a significant improvement at each stage of the research. In the pre-cycle stage, the average ability of children to recognize numbers was still relatively low at 22.2%. After the implementation of the action in Cycle I, the percentage increased to 72.2%, and in Cycle II, it showed a more significant improvement, reaching 89.95%. This improvement was supported by the use of educational game media through a smart board. The method proved effective in enhancing children's number recognition skills. Based on these findings, it can be concluded that the use of play activities, visual media, and repetitive practice can improve children's understanding of numbers.